Criminal Law Enforcement of Motor Vehicle Drivers in Traffic Accidents Resulting in Deaths - Susilawati Susilawati; Abdul Halim; Subroto Rindang Arie Setyawan (Jurnal Restorasi : Hukum dan Politik, 2024)
Traffic accidents resulting in fatalities continue to increase in Indonesia, making it a serious problem that requires special attention in law enforcement. This research explores law enforcement against drivers who cause fatal accidents, based on Law No. 22/2009 on Road Traffic and Transportation. This law requires formal legal resolution through criminal justice for serious accidents, but there are differences with Police Regulation No. 8 of 2021 which allows a Restorative Justice approach for similar accidents, including those resulting in fatalities. This normative research analyzes the alignment of the two regulations and evaluates the application of Restorative Justice as an alternative solution. The results show that the application of Restorative Justice often clashes with formal criminal provisions, so harmonization of regulations is needed so that law enforcement is more consistent and does not neglect the rights of victims and the interests of justice for the community. With the harmonization of laws, it is expected that the police will have a clearer legal basis in handling traffic accident cases in a humanist and comprehensive manner.